2011
DOI: 10.1007/s00784-011-0654-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of microbiota in saliva, supragingival, and subgingival plaque of Chinese adults with chronic periodontitis

Abstract: Examination of bacterial detection frequency and loads in Chinese adults may assist microbial studies of periodontal disease and will shed light on periodontal disease diagnosis and treatment using antibiotics in the Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 49 publications
13
70
1
1
Order By: Relevance
“…gingivalis , in SL were associated with that in SUBP by using a PCR detection-based method [21]. It was also confirmed by later studies using more sophisticated methods, such as quantitative PCR [22] and microarray [23]. Our current results derived by a 16S rRNA gene sequencing approach using a next-generation sequencer contributed further evidence that the analysis of SL provides precise information on the relative difference in abundance and shift of SL.…”
Section: Discussionsupporting
confidence: 78%
“…gingivalis , in SL were associated with that in SUBP by using a PCR detection-based method [21]. It was also confirmed by later studies using more sophisticated methods, such as quantitative PCR [22] and microarray [23]. Our current results derived by a 16S rRNA gene sequencing approach using a next-generation sequencer contributed further evidence that the analysis of SL provides precise information on the relative difference in abundance and shift of SL.…”
Section: Discussionsupporting
confidence: 78%
“…It also contributes to chronic periodontitis. Studies in Chinese, Korean, and southern Thai populations have shown high detection frequencies of A. actinomycetemcomitans ranging approximately from 40% to 75% of the sampling sites [29-32]. In contrast, a study in a Japanese population reported that less than 10% of the chronic periodontitis diseased site was positive for A. actinomycetemcomitans [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the supragingival biofilm samples, P. intermedia, P. nigrescens and P. tannerae were found in 54%, 23.81%, and 64% of the samples, respectively. He et al 18 evaluated matched samples from saliva and supragingival and biofilms in Chinese adults without periodontal disease and observed that G1 (n = 15) G2 (n = 12) G3 (n = 15) G1 (n = 15) G2 (n = 12) G3 (n = 15) G1 (n = 15) G2 (n = 12) G3 (n = 15) 83.3% and 70.8% of the saliva and supragingival samples, respectively, harbored P. intermedia. The presence or absence of an infection in the root canal system did not affect the detection of some species in saliva or supragingival biofilm.…”
Section: Discussionmentioning
confidence: 99%